2017
DOI: 10.1021/acs.jpclett.7b00083
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast Barrierless Photoisomerization and Strong Ultraviolet Absorption of Photoproducts in Plant Sunscreens

Abstract: Sunscreens are aimed at protecting skin from solar ultraviolet (UV) irradiation. By utilizing femtosecond transient absorption spectroscopy and time-dependent density functional theory, we explain nature's selection of sinapoyl malate rather than sinapic acid as the plant sunscreen molecule. In physiological pH conditions, the two molecules are deprotonated, and their excited ππ* states are found to relax to the ground states in a few tens of picoseconds via a barrierless trans-cis photoisomerization. After th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
91
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 77 publications
(93 citation statements)
references
References 24 publications
1
91
1
Order By: Relevance
“…The mixture was recrystallized using a 2 : 1 solution of DCM and petrol (Sigma-Aldrich), to form a light-yellow crystalline product. The resulting compound was analysed using 1 H, 13 C NMR along with X-ray crystallography (see ESI, † Fig. S1-S4).…”
Section: Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…The mixture was recrystallized using a 2 : 1 solution of DCM and petrol (Sigma-Aldrich), to form a light-yellow crystalline product. The resulting compound was analysed using 1 H, 13 C NMR along with X-ray crystallography (see ESI, † Fig. S1-S4).…”
Section: Synthesismentioning
confidence: 99%
“…6 Chemical filters based on cinnamates 7,8 are currently being used as a class of UVR absorbing molecules in commercial formulations due to their strong absorption of UVR and potent antioxidant properties. [9][10][11][12] Investigations into their photochemistry has shown a photoisomerisation pathway as a main route of deactivation, irrespective of solvent environment, [13][14][15][16][17] and starting geometric isomer (either E or Z); 14,18 although a change in lifetimes is noted. One such cinnamate-derivative contained in sunscreen formulations is the FDA and EU approved 2-ethylhexyl-E-4-methoxycinnamate (E-EHMC).…”
Section: Introductionmentioning
confidence: 99%
“…[5] Recently, Luo et al explained the photoprotection mechanism of sinapoyl malate and sinapic acid compounds as the plant sunscreen due to time dependent density functional theory (TD-DFT) approach. [6] It is found that all the excited π-π* states of the three species decay to the ground S0 state nonradiatively via a barrierless trans-cis photoisomerization, which leads to the formation of cis-photoproducts and reduces strongly the efficacy of sinapic acid. The photoprotective property of sinapoyl malate is slightly influenced because the cis-product still absorbs strongly UV light.…”
Section: Introductionmentioning
confidence: 99%
“…The photoprotective property of sinapoyl malate is slightly influenced because the cis-product still absorbs strongly UV light. [6] In this context, the goal of this study is to evaluate free radical scavenging activity and photoprotective mechanism of two acridone derivatives, namely Paratrimerin C (1) and Citrusinine-I (2) (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
“…The completely non-photochemical relaxation of the ES on the femtoseconds cale makes CTAa ne xtraordinarily efficient molecular UV light-to-heate nergy converter without chemical transformation or molecular degradation (see Figure S8). Comparisonw ith natural and synthetic UV absorbers/light stabilizers [6] (cinnamic acid derivatives, [25] b-diketones, [26] benzophenone derivatives, [27] menthyl anthranilate, [28] octocrylene), [29] showst hat the ES relaxation kinetics is faster or at least equally fast in CTA, but most importantly that it proceeds without secondary,l onger-livedp hotoproducts due to keto-enol tautomerization, radical formation, or triplet formation and ensuing singlet oxygen generation. Consequently,C TA might be of interest for applications that demand high UV resistance and filtering.…”
mentioning
confidence: 99%